Comparative assessment of reported symptoms of influenza, respiratory syncytial virus, and human metapneumovirus infection during hospitalization and post‐discharge assessed by Respiratory Intensity and Impact Questionnaire. Issue 1 (2nd September 2021) - Falsey, Ann R.; Walsh, Edward E.; Osborne, Richard H.; Vandendijck, Yannick; Ren, Xiaohui; Witek, James; Kang, Diye; Chan, Eric; Scott, Jane; Ispas, Gabriela
Abstract: Background: The hospitalized acute respiratory tract infection (HARTI) study used the Respiratory Intensity and Impact Questionnaire (RiiQ™) Symptom Scale, derived from FluiiQ™, to assess and compare the burden of respiratory infection symptoms for patients with influenza, respiratory syncytial virus (RSV), and human metapneumovirus (hMPV) infection, with or without core risk factors (CRF) (age ≥65; chronic heart, renal, obstructive pulmonary disease; asthma). Methods: This was a prospective cohort study in adult patients hospitalized with acute respiratory tract infection (40 centers, 12 countries) during two consecutive influenza/RSV/hMPV seasons (2017–2019). The RiiQ™ Symptom Scale and EuroQol 5‐Dimensions 5‐Levels (EQ‐5D‐5L) were assessed by interview at two timepoints during hospitalization and at 1, 2, and 3 months post‐discharge. Results: Mean lower respiratory tract (LRT) symptom scores were higher for RSV and hMPV participants compared to influenza at 48 h after enrollment/early discharge ( p  = 0.001) and 3 months post‐discharge ( p  = 0.007). This was driven by LRT symptoms, including shortness of breath (SOB) ( p  < 0.01) and wheezing ( p  < 0.01) during hospitalization, and SOB ( p  < 0.05) and cough ( p  < 0.05) post‐discharge. Participants with CRF reported more moderate‐to‐severe SOB ( p  < 0.05) and wheezing ( p  < 0.05) compared to CRF(−) participants post‐discharge. EQ‐5D‐5L scores were moderately associated with RiiQ™ LRT and systemic symptoms domains. Conclusions: Results from the HARTI study suggest that in the study population, LRT symptoms were more severe for RSV and hMPV groups and for patients with CRF. RiiQ™ Symptom Scale scores shows a moderate association with EQ‐5D‐5L indicating that the RiiQ™ may provide useful insights and offer advantages over other measures for use in interventional RSV adult clinical studies.